EFEKTIFITAS FIKIH DARURAH DALAM MENYELESAIKAN MASALAH HUKUM KONTEMPORER - Aris, Aris (Jurusan Syariah dan Ekonomi Islam STAIN Parepare, 2011)
This paper is one of the many papers that talk about fiqh darurah. But in the specific context, this paper discusses the effectiveness of Jurisprudence darurah in resolving contemporary legal problems. In that regard, the results of this study to answer two main issues, namely the nature of Jurisprudence darurah and effectiveness in solving the problems of contemporary law. Jurisprudence Discussion darurah not just related to food, even Quranic verses that are directly related to fiqh darurah just talking about food. Jurisprudence darurah it as a proposition or a source of Islamic legislation which can be used to solve the problems of contemporary law. Inserting a row darurah in determining sources of Islamic law means are summarized all events from a variety of situations and circumstances. Jurisprudence darurah have an influence on the legal provisions that already exist and have the determination of the effectiveness in terms of the law to cover complex issues posed by the development of science and technology.